Differing patterns of selection in alternative and constitutive splice sites - Garg, Kavita; Green, Phil

(untitled) (Genome Research, 2007)
In addition to allowing identification of putative functional elements as regions having reduced substitution rates, comparison of genome sequences can also provide insights into these elements at the nucleotide level, by indicating the pattern of tolerated substitutions. We created data sets of orthologous alternative and constitutive splice sites in mouse, rat, and human and analyzed the substitutions occurring within them. Our results illuminate differences between alternative and constitutive sites and, in particular, strongly support the idea that alternative sites are under selection to be weak.